On the poetics of rhythm in arts (and in life) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Review of the book Ritmicidades, cuerpos en JIRA [2015-2019], a collection organized by Carla Fonseca in partnership with the Department of Dramatic Arts of the Universidad Nacional de las Artes (UNA) that brought together the contributions of 22 authors (artists and academics) from different countries that were previously presented during the five editions of the Jornadas Internacionales el Ritmo en las Artes – JIRA (Buenos Aires, 2015-2019). The book was organized with the purpose of putting into theoretical and practical debate the experience of rhythm in various fields of knowledge: epistemology, neuroscience, arts, languages, semiology, psychoanalysis and pedagogy. Ritmicidades is the eloquent record of what was presented, experienced and discussed during all JIRA editions.
Keywords: Rhythm; Embodiment; Art; Philosophy; Science; Pedagogy